Thinking with Balibar : a Lexicon of Conceptual Practice - Stoler, Ann Laura; Gourgouris, Stathis, 1958-; Lezra, Jacques, 1960- (Idiom (Fordham University Press), 2020)
This volume, the first sustained critical work on the French political philosopher Étienne Balibar, collects essays by sixteen prominent philosophers, psychoanalysts, anthropologists, sociologists, and literary critics who each identify, define, and explore a central concept in Balibar's thought.